Stochastic bridge approach for generating correlated time series and its applications - HU Luo-quan; ZHU Hong-bo (Tongxin xuebao)
According to the propagation properties of electromagnetic wave in wireless channels, correlated time series generated by stochastic bridge processes were proposed. The basic random variables with special probability density functions constructed from these time series were produced, which could be used to model wireless propagation channels. The statistical characteristics of basic random variables constructed from free Brownian bridge process and bounded Brownian bridge process, and from free Langevin bridge process and bounded Langevin bridge process were investigated in detail from the numerical simulation, respectively. There were apparently locally favorable peaks in probability density function of basic random variables with lower reflections. Finally, the applications of basic random variables in modeling wireless channels were discussed.